The influence of social psycholinguistic in the interpretation of inscription stone of Machap Melaka 1907 - Kamaruddin, Rohaidah; A Razak, Mohd Rizal Helmi; Ahmad, Nurul Ain; Yajib, Siti Izarina; Goyi, Nalmon; Abdul Rahman, Saiful Nujaimi; Tuan Abd Hamid, Tuan Nur Aisyah (Associação Acadêmica de Propriedade Intelectual, Brazil, 2022)
Psycholinguistics is a knowledge field that describes speech processes while a person speaks. Besides that, this field also study how human acquire speaking ability to extend of influencing the listener or reader. The field also play as the medium to connect language function with human thoughts. Social psycholinguistic is a subtopic in psycholinguistic field that relates basic mentality and society, between psychology, linguistic and social discipline. Social psycholinguistic is not only discussing about language aspect, but also about the relation of social language aspect. The researcher will carry out a study on the psycholinguistic influences in the Batu Bersurat Machap Melaka 1907 interpretation. The objective of this study is to identify and analyse social psycholinguistic influence in the Batu Bersurat Machap Melaka interpretation. Batu Bersurat Machap is one of the research materials and the researcher uses content analyse method to find the data. The findings show that there are social psycholinguistic influences in the interpretation of Batu Bersurat Machap especially from their belief aspect that has been practiced by Malay society especially in the use of 'keramat' and 'pelaris' in their business.